Cold Acclimation for Enhancing the Cold Tolerance of Zebrafish Cells - Wang, Huamin; Wang, Ying; Niu, Minghui; Hu, Linghong; Chen, Liangbiao (Frontiers in Physiology, 2022)
Cold stress is an important threat in the life history of fish. However, current research on the tolerance mechanisms of fish to cold stress is incomplete. To explore the relevant molecular mechanisms enabling cold stress tolerance in fish, here we studied ZF4 cells subjected to short-term (4 days) low temperature stress and long-term (3 months) low temperature acclimation. The results showed that cell viability decreased and the cytoskeleton shrank under short-term (4 days) low temperature stress, while the cell viability and the cytoskeleton became normal after cold acclimation at 18°C for 3 months. Further, when the cells were transferred to the lower temperature (13°C), the survival rate was higher in the acclimated than non-acclimated group. By investigating the oxidative stress pathway, we found that the ROS (reactive oxygen species) content increased under short-term (4 days) cold stress, coupled with changes in glutathione (GSH), catalase (CAT), superoxide dismutase (SOD) enzyme activity levels. In addition, overproduction of ROS disrupted physiological cellular homeostasis that generated apoptosis via the activation of the mitochondrial pathway. However, when compared with the non-domesticated group, both ROS levels and apoptosis were lowered in the long-term (3 months) domesticated cells. Taken together, these findings suggest that cold acclimation can improve the low temperature tolerance of the cells. This exploration of the mechanism by which zebrafish cells tolerate cold stress, thus contributes to laying the foundation for future study of the molecular mechanism of cold adaptation in fish.